Contrastación de medidores para clientes de la zona urbana de la Unidad de Negocios Los Ríos - Vaca Haro, Juan Carlos (2018)
The testing of energy meters consists of determining the degree of accuracy with which the meter records the energy, and if necessary adjust it so that the error is within the limits established by the corresponding standards, in general all energy meters they must be checked before being installed, but in some occasions these same meters are manipulated by the user or are defective, this is why the initiative is taken to contrast those already in use. For this, the devices for the verification, calibration or performance of other tests on instruments or measuring systems, such as testing of instruments, meters or measuring systems that comply with at least the indicated references, will be used. The preventive and corrective maintenance of the devices for the verification and testing of the measurement instruments or systems is carried out, for which they must use the services of a duly accredited entity such as Cnel. Ep. The standards and instruments possessed by the devices for the verification and calibration of the measuring equipment may not be manipulated, modified or altered in any way. The contracting entity for the control of the measuring equipment will select the users subject to the verification of the electric power meter of a specific area, this selection will be made applying statistical criteria and geographic location. The contracted entity or selected company will be the one that will carry out the different replacement activities or changes of defective or damaged meters, informing the officials of the Business Unit (of the concessionaire and the testing entity) in charge of coordinating the supervision activities.